PENGARUH PENDIDIKAN TERHADAP KEHIDUPAN KELUARGA - Syamsul Hadi Thubany (Jurnal Sosiologi Reflektif, 2013)
The presence of educational institutions (schools) are functionally has adversely affected the family as the pattern of relationships among members, roles and functions as well as life style. Some of the most striking is the pattern of the child and parent relationship, in which the authority of parents in educating children mostly have taken over the school. So, come up emancipation of women who dared to break the patriarchal culture, and the independence of the nuclear family that does not want to be intervened by a extended family. It is important that the phenomenon of changes in the family’s social formation in turn would affect the social structure in which the jib is one of a family unit.